Singing Democracy and Politics in Post-Independence Zimbabwe: A Critical Discourse Analysis of Self-censorship in Zimbabwean Indigenous Theological-Sungura Music - Mutingwende, Andrew; Jakaza , Ernest (Palgrave Macmillan Cham, 2022)
The chapter is premised on the discursive nature of African indigenous popular music and the way Zimbabwean artistes engage in self-censorship in articulating and promoting democratic and egalitarian culture in post-independence Zimbabwe. The central focus is entrenched upon the development that the Zimbabwean artists’ target audience is bifurcated in two heterogeneous camps: the sublime suspect group constituting the central force being called to right a wrong and the marginalised subgroup. The chapter engages the Critical Discourse Analysis (CDA) theory to examine the effect of a marginalised and hybridised Zimbabwean music genre: Theological-Sungura and its discursive articulation towards the propagation of a virtually utopian and democratic socio-political terrain. Qualitative purposive sampling of Zimbabwean Theological-Sungura artists is carried out. This chapter argues that Theological-Sungura can be truncated from both porous mains as an emergent daughter genre and that this genre is inwardly militant in its promulgation of democracy and socio-political pluralism. The genre acquires a more conciliatory and euphemistic censure for a rhetorical function promoting harmony and conflict-free socio-political landscape.